PURWARUPA SISTEM PEMBATAS KECEPATAN SEPEDA MOTOR BERBASIS MIKROKONTROLER AT89S52 - Ikhsan hidayat; Abdul Fadlil; Edy Fathurrozaq (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Security riding is very important in the aspects of traffic. One of the main factors of traffic accidents is high speed. Therefore, it is required a speed restraint equipment for pressing the number of accidents. The car speed restraint system is available in the market, but on a motorcycle is not available yet. This paper presents a design of speed restraint equipment for motorcycle that safe for users, and is expected to reduce traffic accident. The Main idea this speed restriction is cutting off the flow of electrical signals from the pulser (the time ignition trigger sensor) to the CDI for 1 second. The cutting Signal with mechanical relays controlled by microcontroller AT89S52 using the on-off algorithm. Speed sensor use optocoupler is used to detect the number of rounds wheel motorcycle. If a result of measurement is more than the speed setpoint, microcontroler make a decission to cut motorcycle ignition signal. Results of this research is a prototype speed restraint shown that it able to process data from the measurement of the speed limit on the speed of a motorcycle. This prototype safe for all users and accordance with the set value and the level of success is above 90% for speed of 10 km/hr to 40 km/hr.